Margem Esquerda 34 - REA, Editor (Revista Espaço Acadêmico, 2020)
Título: Margem Esquerda 34 Autores: Anselm Jappe, David Harvey, Michael Löwy, Tithi Bhattacharya, Noam Chomsky Páginas: 160 ISBN: 9771678768400 Ano de lançamento: 2020 Editora: Boitempo